The larva of Chaetopteryx rugulosa Kolenati 1848 (Trichoptera: Limnephilidae), with notes on ecology and zoogeography - Zweidick, Oliver; Graf, Wolfram; Waringer, Johann (Zootaxa, 2020)
This paper gives a description of the hitherto unknown larva of Chaetopteryx rugulosa Kolenati 1848 (Trichoptera: Limnephilidae). Information on the morphology of the larva is given, and the most important diagnostic features are figured. In the context of the known European Chaetopterygini and Stenophylacini species, the larva of C. rugulosa can be separated from morphologically close species by metanotal sclerite morphology, setation, the extension of the lateral fringe, and by case morphology.